2021
DOI: 10.1080/00221309.2021.1874864
|View full text |Cite
|
Sign up to set email alerts
|

Typologies of coping in young adults in the context of the COVID-19 pandemic

Abstract: The COVID-19 pandemic has created major upheavals in the lives of people worldwide. The virus has mostly affected elderly populations, but there may be corollary effects on young adults' psychosocial adjustment due to educational, economic, and occupational disruptions. Using latent class analysis, we examined unique typologies of coping in response to the pandemic among young adults. We used an expanded set of indicators including traditional measures of problem-and emotion-focused coping as well as measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 90 publications
1
24
0
2
Order By: Relevance
“…Combined with uncertainty as a pandemic-related stressor, loss of control emerges as highly relevant for well-being research during COVID-19 as well (e.g., Chen & Bonanno, 2020;Shigemura et al, 2020). For instance, the perceived uncontrollability of the pandemic relates to both flexible coping and resilience (Shigeto et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with uncertainty as a pandemic-related stressor, loss of control emerges as highly relevant for well-being research during COVID-19 as well (e.g., Chen & Bonanno, 2020;Shigemura et al, 2020). For instance, the perceived uncontrollability of the pandemic relates to both flexible coping and resilience (Shigeto et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In times of extraordinary strain, such as the pandemic, resilience may be the key to handling stressors and minimising their impact (Bonanno, 2020). However, not everyone possesses such resources, leading to individual differences (Chen & Bonanno, 2020;Shigeto et al, 2021). For instance, more resilient medical students perceived less stress (Pollak et al, 2020).…”
Section: Students' Resilience In Pandemic Timesmentioning
confidence: 99%
“…Participants were recruited using two methods: Amazon’s Mechanical Turk (MTurk) labor pool (i.e., an online platform where participants can complete simple tasks such as surveys in exchange for monetary compensation) and snowball sampling through University colleagues and research assistants. Regardless of recruitment method, all participants were screened to ensure that they were between the ages of 18 and 35 (details on the recruitment and screening procedures are presented in [ 41 ]). The project was approved by the University Institutional Review Board (IRB) at the first author’s institution, and carried out in accordance with the ethical guidelines of the American Psychological Association.…”
Section: Methodsmentioning
confidence: 99%
“…The survey employed a randomized three-form planned missingness design [ 43 , 44 ] to keep the length of the survey manageable. Each participant responded to either 71 or 73 items, approximately two-thirds of the total number of items (for more detail, see [ 41 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Although previous findings imply a key role of flexibility in successful coping with trauma, which is informative for identifying potential predictors for coping with the COVID-19 pandemic, and the widely held belief that flexibility is particularly critical for coping with multidimensional long-term stressors, only few studies have examined how flexibility may influence coping with the COVID-19 pandemic. First studies investigating the impact of trauma-related regulatory flexibility (Cheng et al, 2021;Jordan et al, 2021;Shigeto et al, 2021) and cognitive flexibility (Kalia et al, 2020;Seiter & Curran, 2021) on responses to the COVID-19 pandemic revealed that low flexibility is linked to more negative responses.…”
Section: Coping With Covid-19mentioning
confidence: 99%